PENERAPAN SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) KEUANGAN TERHADAP EFEKTIVITAS PELAPORAN KEUANGAN (Studi pada Badan Pengelolaan Keuangan dan Aset Daerah Di Kabupaten Blitar) - Yogi Hertanto; Tjahjanulin Domai; Fadillah Amin (Universitas Merdeka Malang, 2017)
The presence of SIMDA of Finance is expected to be contribute towards the process of financial management, particularly at the stage of financial reporting should be able to running better. The ideal management information system is able providing a support to the process of planning, control and decision making. In addition the effectiveness of financial reporting has to fullfil several criteria, which is reliable, accuracy / accurate, timely and report forms. This study was conducted to analyze the role of SIMDA towards the effectiveness of the financial reporting process, and the factors that influence it. This study uses qualitative data to describe and analyze objectives: Implementation of Regional Management Information System (SIMDA) of Finance toward the Effectiveness of Financial Reporting In Badan Pengelolaan Keungan dan Aset Daerah of Blitar Distric. Data was collected by using an interview, observation and documentation. Results from this study indicate that the SIMDA of Finance Aplication in the process of financial management, especially the financial reporting work better but still could not said to be fully effective, this is because of the presence of various obstacles are still fundamentally highly influential in the implementation SIMDA of Finance AplicationDOI: https://doi.org/10.26905/pjiap.v2i1.1424